Lymphocyte to C-reactive protein ratio is associated with in-hospital cardiac death in elderly patients with non-ST-segment elevation myocardial infarction - Luo, Jun; Shao, Han; Song, Yu; Chao, Yali (Frontiers in Cardiovascular Medicine, 2024)
Background Although percutaneous coronary intervention (PCI) is recommended by guidelines, data from the real world suggest that elderly non-ST-segment elevation myocardial infarction (NSTEMI) patients have a low rate of PCI and a high death rate. Lymphocyte to C-reactive protein ratio (LCR), a novel inflammatory marker, has been shown to be associated with prognosis in a variety of diseases. However, the relationship between LCR and in-hospital cardiac death in elderly NSTEMI patients is unclear. The aim of this study was to investigate the effect of LCR on in-hospital cardiac death in elderly NSTEMI patients without PCI therapy. Methods This was a single-center retrospective observational study, consecutively enrolled elderly (≥75 years) patients diagnosed with NSTEMI and without PCI from February 2019 to February 2024. LCR was defined as lymphocyte count to C-reactive protein ratio. The endpoint of observation was in-hospital cardiac death. The predictive efficacy of the old and new models was evaluated by the net reclassification index (NRI) and the integrated discriminant improvement index (IDI). Results A total of 506 patients were enrolled in this study, and in-hospital cardiac death occurred in 54 patients (10.7%). Univariate logistic regression analysis showed that left ventricular ejection fraction, LCR, Killip ≥2, and N-terminal B-type natriuretic peptide proteins (NT-proBNP) were associated with the occurrence of in-hospital cardiac death. After adjusting for potential confounders, the results showed that NT-proBNP (OR = 1.695, 95% CI: 1.238–2.322) and LCR (OR = 0.262, 95% CI: 0.072–0.959) were independent risk factors for in-hospital cardiac death. After the addition of LCR to NT-proBNP, the predictive ability of the new model for in-hospital cardiac death was significantly improved (NRI = 0.278, P = 0.030; IDI = 0.017, P < 0.001). Conclusion Lower LCR is an independent risk factor for in-hospital cardiac death in elderly NSTEMI patients without PCI, and integrating LCR improves the prediction of in-hospital cardiac death occurrence.